ANALISIS MODEL KEPUASAAN CIVITAS AKADEMIKA TERHADAP PELAYANAN PERPUSTAKAAN DI FAKULTAS SAINS DAN TEKNOLOGI UNIVERSITAS JAMBI DENGAN METODE STRUCTURAL EQUATION MODELING (SEM) - Sherli Yurinanda; Syamsyida Rozi; Sarmada Sarmada (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Service quality comes from a comparison between customer expectations about the service they should receive with the service they actually get. An important service unit in state universities such as the University of Jambi is the library service. The library is a service unit that provides services in the field of literature. The needs of library users, especially students, for science and other educational media are difficult to separate. Therefore, the library is one of the academic support facilities needed by library users such as students and lecturers. Based on the results of observations, various efforts have been made by the FST UNJA’s Library to improve services, but these improvements are still not optimal. Therefore, it is necessary to analyze the factors that influence service quality to assist the FST UNJA’s Library in reviewing the factors that affect service quality. The Structural Equation Modeling (SEM) method is a multivariate statistical method that can be used to look at the factors that influence the quality of the service. SEM is an appropriate analysis used in social research. In this study, there are two exogenous variables used, the first is employee competency which has manifest variables to measure it, such as knowledge, understanding, ability and attitude. The second is library facilities that have manifest variables to measure them, namely library space, library equipment and reading book collections. As well as the endogenous variables used in this study is the quality of service which has five manifest variables of reliability, responsiveness, assurance, empathy and tangible. The research data is primary data obtained by researchers by distributing questionnaires to visitors to the FST UNJA’s library